1989
DOI: 10.1084/jem.169.3.677
|View full text |Cite
|
Sign up to set email alerts
|

Human T cell activation. IV. T cell activation and proliferation via the early activation antigen EA 1.

Abstract: The tumor promoter PMA has been shown to induce accessory cell-independent T cell proliferation in conjunction with mAbs specific for CD3, CD28, and CD2 (1-6) . In these systems, PMA induces IL-2-R expression while the presence of these mAbs is synergistic for the maximal expression of IL-2-R and IL-2 production.Recently, we have identified the early activation antigen, EA 1, by the generation of mAb specific for PMA-activated T cells (7). EA 1 expression is seen as early as 30 min after the addition ofPMA. EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 22 publications
(7 reference statements)
0
19
0
1
Order By: Relevance
“…47 Activated Ras plays a central role for cell-surface expression, 48 which reaches a maximum at 18 to 24 hours after stimulation. 49,50 Although the function of CD69 has not been ultimately defined, cross-linking studies have demonstrated a role for CD69 in regulating the production of T-cell activating cytokines such as IL-2 51 as well as the IL-2 receptor (CD25), 52 interferon ␥, and tumor necrosis factor-␣. 53 Among other alterations of the cytokine network observed after TCD therapy, 3,54 a decrease of IL-2 production 36,37,55 as well as of transcription examined on a single-cell basis 56 may be of particular relevance to the disturbed T-cell function.…”
Section: Discussionmentioning
confidence: 99%
“…47 Activated Ras plays a central role for cell-surface expression, 48 which reaches a maximum at 18 to 24 hours after stimulation. 49,50 Although the function of CD69 has not been ultimately defined, cross-linking studies have demonstrated a role for CD69 in regulating the production of T-cell activating cytokines such as IL-2 51 as well as the IL-2 receptor (CD25), 52 interferon ␥, and tumor necrosis factor-␣. 53 Among other alterations of the cytokine network observed after TCD therapy, 3,54 a decrease of IL-2 production 36,37,55 as well as of transcription examined on a single-cell basis 56 may be of particular relevance to the disturbed T-cell function.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CD69 is a C-type lectin (Lopez-Cabera et al, 1993) likely to contribute to adhesion and CD38 has been implicated in binding to endothelium (Xu et al, 1994). Furthermore, both CD69 and CD38 are involved in signal transduction and cell activation (Nakamura et al, 1989;Moretta et al, 1991;Tugores et al, 1992;Xu et al, 1994) and CD30, a member of the TNF receptor family, could modulate TIL effector function by interacting with the CD30 ligand in the tumour (Faustman et al, 1982).…”
Section: Tils Display Strong Activation-independent Binding To Endothmentioning
confidence: 99%
“…In the case of T cells, the addition of anti-CD69 MAbs enhanced anti-CD3 and PMA-induced proliferation [23][25] through increased interleukin (IL)-2 and IL-2 receptor expression [26] [4]. However a later study using CD69 −/− mice argued against such a role, since Ag-specific T cell proliferation was unaffected in vivo [27].…”
Section: Introductionmentioning
confidence: 99%